The Application of Zeolites for Fixation of Cr(VI) Ions in Sediments - Marjana Simonič (Physchem, 2025)
The aim of the study was to investigate the fixation of Cr(VI) ions from contaminated sediments using synthetic zeolite 4A and natural zeolite clinoptilolite. Parameters such as pH, contact time, adsorption mass and temperature were investigated. If the ions of the heavy metals were mobile, they would become toxic to the environment. After sediment digestion, the initial and final concentrations of Cr(VI) were measured in sediment samples with or without zeolite. Inductively coupled plasma with optical emission spectroscopy (ICP-OES) and X-ray diffraction (XRD) were used to characterize the material. The adsorption kinetics were investigated using a pseudo-first order model, a pseudo-second order model, and an intra-particle diffusion model. The results showed that the zeolites enhanced the fixation of Cr(VI). Chemisorption was the main mechanism when using acid-modified zeolite.